Why Engagement Matters in Sport Volunteer Motivation - Marcella G Otto; J. Michael Martinez; Chris R Barnhill (Journal of Applied Sports Management, 2022)
Over the years, sport management scholars have been interested in sport volunteer research. Considering there is a heavy reliance on sport volunteers to successfully stage of sporting events, knowing how to recruit and retain these volunteers allows sport event managers and organizers to continue this success. One such way is through understanding the engagement of sport volunteers, specifically the influences of engagement. Through survey methodology, this study examined how engagement of 464 sport volunteers at college football bowl games influenced motivational aspects. Structural Equation Modeling found that meaningfulness and safety had a significant impact on love and purposive motivation through engagement, but there was no significant relationship with rewards. With these results in mind, there are implications for sport event organizers to remember when working with volunteers. Keywords: Human resource management, volunteer engagement, volunteer motivation
Keywords: Human resource engagement; volunteer engagement; volunteer motivation